Essays in unit root testing - Smith, Lynette Vanessa (2003)
This thesis is a collection of four essays with main focus on testing for a unit root under structural change, and on the behaviour of power-enhancing unit root tests that have recently emerged as a solution to the well-known power deficiency of traditional such tests. New tests and variants of commonly applied ones are introduced in response to the need for reliable statistical techniques in modelling economic series over time.